Composition for resin raw materials
Patent Information
- Application Number
- KR1020227003662
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-21
- Filing Date
- 2020-08-17
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2040-08-17
Smart Images

Figure 112022011945615-PCT00001 
Figure 112022011945615-PCT00002 
Figure 112022011945615-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a composition for resin raw materials used to manufacture resins with excellent mechanical properties. Background Technology
[0002] Polyimide is widely used in various electronic devices, such as substrates for flexible printed circuits (FPC), substrates for tape-automated bonding (TAB), protective films for semiconductor devices, and interlayer insulating films for integrated circuits, as it possesses excellent heat resistance as well as chemical resistance, radiation resistance, electrical insulation, and excellent mechanical properties. In addition to these properties, polyimide has recently gained increasing importance due to its simple manufacturing method, very high film purity, and ease of improving properties using various available monomers.
[0003] The compound represented by the chemical formula a below, 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride) (hereinafter referred to as “compound a”), is a compound useful as a raw material for polyesterimide resins that combines a high glass transition temperature, a low coefficient of linear thermal expansion equivalent to that of metal foil, a very low water absorption rate, a high elastic modulus, sufficient toughness, and sufficient adhesion to metal foil (e.g., Patent Documents 1 and 2).
[0004] [Chemical formula a]
[0005] Prior art literature
[0006] Japanese Patent Publication No. 2014-001394, International Publication No. 2014 / 046180 The problem to be solved
[0007] When polyesterimide resin is manufactured using compound a as a raw material, there were cases where the mechanical properties of the obtained resin varied significantly, even though the resin was manufactured by the same manufacturing method. For this reason, there was a need to provide a composition for resin raw materials capable of manufacturing polyesterimide resin with more robust mechanical properties.
[0008] Conventionally, regarding impurities included as by-products in the synthesis reaction process or purification process of compound a, the effect of these impurities when additionally used in polyesterimide resin is not known at all, and no investigation has been conducted.
[0009] The present invention was made against the background of the aforementioned circumstances and aims to provide a composition for resin raw materials that enables the production of a polyesterimide resin with significantly superior mechanical properties compared to conventional materials. means of solving the problem
[0010] As a result of careful consideration to solve the aforementioned problem, the inventors discovered that certain impurities contained in 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride) affect the mechanical properties of the resulting polyesterimide resin, and thus completed the present invention.
[0011] The present invention is as follows.
[0012] 1. A composition for a resin raw material containing, as component A, a compound represented by the following chemical formula a, and as component B, a compound represented by the following chemical formula b, in the following compositional ratios.
[0013] [Composition ratio]: With respect to the total amount of all components detected by measurement by gel permeation chromatography using a differential refractometer as a detector, component A is 99.0 area% or more and 99.99 area% or less, and component B is 0.005 area% or more and 0.4 area% or less.
[0014] [Chemical formula a]
[0015]
[0016] [Chemical formula b]
[0017]
[0018] (In the formula, R represents a hydrogen atom or R1-CO- (where R1 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
[0019] 2. A method for manufacturing polyesterimide, comprising a process (i) of obtaining a polyesterimide precursor by reacting a composition containing, in the following compositional ratios, a compound represented by the chemical formula a as component A and a compound represented by the chemical formula b as component B, with a diamine, and then a process (ii) of imidizing the same.
[0020] [Composition ratio]: With respect to the total amount of all components detected by measurement by gel permeation chromatography using a differential refractometer as a detector, component A is 99.0 area% or more and 99.99 area% or less, and component B is 0.005 area% or more and 0.4 area% or less.
[0021] [Chemical formula a]
[0022]
[0023] [Chemical formula b]
[0024]
[0025] (In the formula, R represents a hydrogen atom or R1-CO- (where R1 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms). Effects of the invention
[0026] According to the present invention, it is possible to provide a composition for a resin raw material capable of producing a polyesterimide resin with significantly superior mechanical properties compared to conventional materials. Furthermore, based on the discovery that specific impurities affect mechanical properties, it is possible to produce a polyesterimide resin having more robust mechanical properties from a composition for a resin raw material in which such specific impurities are reduced. Specific details for implementing the invention
[0027] The present invention is described in detail below.
[0028] <Ingredient A>
[0029] The composition for resin raw materials of the present invention contains, as component A, compound a “2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride)” represented by the following chemical formula a as a main component.
[0030] [Chemical formula a]
[0031]
[0032] The content of component A in the resin raw material composition of the present invention is 99.0 area% or more and 99.99 area% or less with respect to the total amount of all components detected by measurement using gel permeation chromatography with a differential refractometer as a detector. The lower limit is preferably 99.1 area% or more, and more preferably 99.3 area% or more.
[0033] <Ingredient B>
[0034] The composition for resin raw materials of the present invention contains, as component B, a compound represented by the following chemical formula b, in a range of 0.005 area% or more and 0.4 area% or less relative to the total amount of all components detected by measurement using gel permeation chromatography with a differential refractometer as a detector. The upper limit is preferably 0.35 area% or less, more preferably 0.3 area% or less, even more preferably 0.2 area% or less, and particularly preferably 0.15 area% or less. In addition, the lower limit may be 0.01 area% or more from the perspective of suppressing a decrease in the quantity of component A, which is the target product, when repeated purification is performed.
[0035] Polyesterimide resin obtained using a composition for resin raw materials containing more than 0.4 area% of the compound represented by the chemical formula b below according to the above measurement has significantly reduced mechanical properties.
[0036] [Chemical formula b]
[0037]
[0038] (In the formula, R represents a hydrogen atom or R1-CO- (where R1 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
[0039] As a specific example of component B in the composition for resin raw materials of the present invention, for instance, the following compound b1, in which "R" in the above chemical formula b is a hydrogen atom, may be cited.
[0040] [Chemical formula b1]
[0041]
[0042] The above compound b1 is a compound produced as a reaction intermediate when synthesizing compound a by the "acid halide method," which is one of the methods for preparing a resin raw material composition of the present invention, described below. The reaction equation for the production of compound b1 by the "acid halide method" is shown below.
[0043]
[0044] In addition, as a specific example of component B in the composition for resin raw materials of the present invention, for example, the following compound b2, in which “R” in the above formula b is R1-CO- and “R1” is an alkyl group having 1 carbon atom, can be cited.
[0045] [Chemical Formula 2]
[0046]
[0047] The above compound b2 is a compound produced as a reaction intermediate when synthesizing compound a by the "ester exchange method," which is one of the methods for manufacturing a resin raw material composition of the present invention, described below.
[0048] The reaction equation for the formation of compound b2 by the "ester exchange method" is shown below.
[0049]
[0050] In addition, the above compound b2 is also a compound produced when compound b1 reacts with acetic anhydride in the reaction post-treatment process of the aforementioned "acid halide method."
[0051] The reaction equation is shown below.
[0052]
[0053] <Manufacturing Method 1: "Acid Halide Method">
[0054] One of the methods for manufacturing the resin raw material composition of the present invention, the "acid halide method," is described below.
[0055] This “acid halide method” is a method for preparing a composition for resin raw materials of the present invention, which has compound a as the main component, by reacting 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with trimellitic acid halide anhydride, as shown in the reaction scheme below.
[0056]
[0057] Examples of trimellitic anhydride halides used in the above "acid halide method" include trimellitic anhydride chloride (equivalent to the compound in the above reaction formula), trimellitic anhydride bromide, trimellitic anhydride iodide, and trimellitic anhydride fluoride. Among these trimellitic anhydride halides, trimellitic anhydride chloride is suitablely used because it is inexpensive and readily available.
[0058] The amount of these trimellitic anhydride halides used is typically 2 to 3 moles per 1 mole of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, and preferably 2.1 to 2.5 moles.
[0059] In the above "acid halide method," since hydrogen halides are generated by the reaction of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with trimellitic acid halide anhydride, a base is used to capture them. Such a base is not particularly limited, but it is possible to use organic tertiary amines such as pyridine, triethylamine, and N,N-dimethylaniline, epoxy compounds such as propylene oxide, and inorganic bases such as potassium carbonate and sodium hydroxide. Among these, pyridine is suitably used from the perspective of separation operations after the reaction, cost, and hazards.
[0060] The above "acid halide method" initiates a reaction by mixing a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, which is a solvent of the same type, with anhydrous trimellitic acid halide dissolved in a solvent. At this time, a base such as pyridine is contained in the solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, which is the solution being mixed. Furthermore, contrary to the above mixing method, if a solution of anhydrous trimellitic acid halide is mixed into a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, by-products are more likely to be formed than in the former mixing method. Therefore, the former mixing method, that is, mixing a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol dissolved in a solvent with a solution of anhydrous trimellitic acid halide dissolved in a solvent, is preferred.
[0061] It is preferable that the molar ratio of the starting material and the base used in the reaction be within the range of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol / trimellitic acid halide / base 1.0 / 2.1∼2.5 / 3.0∼5.0.
[0062] The mixing of each of the above solutions is performed at a low temperature. The temperature within the reaction system is preferably in the range of -10 to 10°C, more preferably in the range of -5 to 7°C, and particularly preferably in the range of 0 to 5°C. There are no restrictions on the time required for mixing, but 2 to 4 hours is preferred.
[0063] Stirring (hereinafter referred to as "post-stirring 1") immediately after the completion of mixing of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol and trimellitic acid halide anhydrous is to be continuously carried out at a low temperature, preferably within a temperature range of -10 to 10°C, more preferably within a range of -5 to 7°C, and particularly preferably within a range of 0 to 5°C. "Post-stirring 1" is preferably carried out within approximately 5 hours within this temperature range, and among these, 2 to 3 hours is more preferably
[0064] After this "post-stirring 1," to promote the reaction, stirring may be continued at a higher temperature than "post-stirring 1" (hereinafter referred to as "post-stirring 2") to complete the reaction. It is preferable to perform "post-stirring 2" at a temperature within the reaction system in the range of 50 to 75°C, more preferable to perform it in the range of 55 to 70°C, and particularly preferable to perform it in the range of 60 to 65°C. It is preferable to perform "post-stirring 2" within this temperature range for approximately 5 hours, and among these, 2 to 3 hours is more preferable.
[0065] As for solvents that can be used in the above "acid halide method," they are not particularly limited as long as they do not inhibit the reaction, but examples include aprotic solvents such as tetrahydrofuran, 1,4-dioxane, picoline, pyridine, acetone, chloroform, toluene, xylene, dichloromethane, 1,2-dichloroethane, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, hexamethylphosphoramide, dimethyl sulfoxide, γ-butyrolactone, γ-valerolactone, 1,3-dimethyl-2-imidazolidinone, 1,2-dimethoxyethane-bis(2-methoxyethyl)ether, and acetonitrile. In addition, these solvents may be used individually or in a mixture of two or more types. Among these, tetrahydrofuran, γ-butyrolactone, γ-valerolactone, acetonitrile, etc. are suitably used in order to carry out the reaction rapidly and suppress the retention of compound b1, which is a reaction intermediate.
[0066] <Manufacturing Method 2: "Ester Exchange Method">
[0067] One of the methods for manufacturing the resin raw material composition of the present invention, the "ester exchange method," is described below.
[0068] This “ester exchange method” is a method for preparing a composition for resin raw materials of the present invention, which has compound a as the main component, by reacting a dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with trimellitic anhydride, as shown in the reaction scheme below.
[0069]
[0070] (In the formula, R1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
[0071] As for the dicarboxylic acid esters of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol used in the above "ester exchange method," specifically, for example, 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(acetate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(propionate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(butyrate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(benzoate), Examples include 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(naphthoate).
[0072] These dicarboxylic acid esters of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol can be prepared by conventionally known methods, for example, by reacting 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with a carboxylic acid anhydride or a carboxylic acid halide.
[0073] The amount of mus trimellitic acid used in the above “ester exchange method” is typically 2 mole times or more, preferably in the range of 2 to 10 mole times, and particularly preferably in the range of 2.6 to 3.4 mole times, per 1 mole of the dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol.
[0074] The reaction temperature of the above "ester exchange reaction" is typically in the range of 100 to 300°C, preferably in the range of 150 to 250°C, and particularly preferably in the range of 200 to 230°C.
[0075] In the above "ester exchange method," it is preferable to use a base as a catalyst in the reaction. Specifically, as these bases, examples include inorganic alkali metal compounds such as alkali metal hydroxides, carbonates, and bicarbonate compounds, and organic alkali metal compounds such as alkali metal alcohols, phenols, and salts with organic carboxylic acids. Specifically, examples include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, lithium acetate, sodium acetate, potassium acetate, etc.
[0076] The amount of these bases used is in the range of 0.001 to 10 mol%, preferably 0.005 to 5 mol%, per 1 mol of the dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol.
[0077] In the above "ester exchange method," it is preferable to use a reaction solvent during the reaction for reasons such as improved operability or reaction rate during industrial production. As for the solvent that can be used, there are no particular restrictions as long as it does not leak out of the reaction vessel at the above reaction temperature and is inert to the ester exchange reaction. Specifically, examples include aromatic hydrocarbon ether-based solvents such as alkylaryl ethers such as phenetol and butylphenyl ether, diaryl ethers such as diphenyl ether and di-p-tolyl ether, aromatic hydrocarbon solvents such as biphenyl and terphenyl, alkyl-substituted naphthalenes such as diisopropylnaphthalene, aliphatic hydrocarbons such as decalin and kerosene, polyalkylene glycol ethers such as tetraethylene glycol dimethyl ether and diethylene glycol dibutyl ether, and organic solvents such as the Thumb-S series (manufactured by Shin-Nippon Chemical Co.), KSK-OIL series (manufactured by Soken Chemical Co.), or Neo SK-OIL series (manufactured by Soken Chemical Co.). When using these solvents, the amount used is typically in the range of 1 to 10 parts by weight, preferably 2 to 3 parts by weight, per 1 part by weight of the dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol.
[0078] <Refinement>
[0079] The composition for the resin raw material of the present invention can be obtained by purifying the reaction product obtained by the aforementioned reaction in order to make the content of the compound represented by chemical formula b, as component B, within a specific range.
[0080] The purification method may utilize known methods, but it is preferable to perform it by the method of crystallization and reslurry (suspending a solid in a solvent). To achieve a specific content of component B, it is more preferable to repeat these operations multiple times rather than just once. As for the solvents that can be used for crystallization and reslurry, there are no particular restrictions as long as they are inert to component A; specifically, examples include acetic anhydride, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, tetrahydrofuran, methyl isobutyl ether, methyl isopropyl ether, toluene, xylene, ethylbenzene, γ-butyrolactone, γ-valerolactone, acetonitrile, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc. Among these, acetic anhydride, cyclohexanone, and γ-butyrolactone are preferred.
[0081] The conditions for purification vary depending on the solvent used and cannot be stated uniformly, but for example, when γ-butyrolactone is used, the amount of solvent used is in the range of 5 to 50 parts by weight per 1 part by weight of the total amount of the composition containing component A, component B, and other impurities undergoing purification treatment, more preferably in the range of 10 to 30 parts by weight, and particularly preferably in the range of 1 to 20 parts by weight. The temperature during dissolution is in the range of 100 to 200°C, more preferably in the range of 110 to 180°C, even more preferably in the range of 110 to 160°C, and particularly preferably in the range of 120 to 140°C. The cooling temperature is in the range of 0°C to 50°C, more preferably in the range of 10 to 40°C, and even more preferably in the range of 15 to 30°C.
[0082] The conditions for the reslurry method vary depending on the solvent used and cannot be stated uniformly, but for example, when γ-butyrolactone is used, the amount of solvent used is preferably in the range of 2 to 20 parts by weight, more preferably in the range of 2 to 12 parts by weight, and even more preferably in the range of 4 to 8 parts by weight, relative to 1 part by weight of the total amount of the composition containing component A, component B, and other impurities subjected to purification treatment. The treatment temperature is preferably in the range of 100 to 200°C, more preferably in the range of 110 to 180°C, even more preferably in the range of 110 to 160°C, and particularly preferably in the range of 120 to 140°C. The reslurry treatment is preferably carried out for about 0.5 to 3 hours.
[0083] When using other solvents, various conditions can be appropriately changed by considering the boiling point of the solvent, the solubility of component A, component B, other impurities, and the composition containing them, which are subjected to static treatment.
[0084] In addition, it is possible to obtain a high-purity product with further reduced metal components, such as inorganic salts, by filtering a solution containing a composition containing component A, component B, and other impurities before crystallization by purification operations such as the method of crystallization and reslurry, or by washing with water. At this time, even if some or all of the acid anhydride groups of component A and component B are ring-opened and carboxylic acids are formed by contact with water, they can be returned to carboxylic acid anhydrides by heat treatment or by reacting with an acid anhydride such as acetic anhydride.
[0085] Since the purified product obtained by these purification processes may contain the used solvent, it is desirable to remove the solvent and dry it. The method for removing the solvent is not particularly limited, but for example, a method of distilling and removing the solvent by heating under atmospheric pressure or reduced pressure may be cited.
[0086] <Polyesterimide obtained using the resin raw material composition of the present invention>
[0087] Polyesterimide can be produced by a process (i) of obtaining a polyesterimide precursor (polyamic acid) by reacting the composition for the resin raw material of the present invention with a diamine, followed by a process (ii) of imidizing it.
[0088] <(i) Process for obtaining polyesterimide precursor (polyamic acid) >
[0089] As a process for obtaining a polyesterimide precursor, a reaction is carried out between the composition for resin raw materials of the present invention and a diamine. As a specific method thereof, for example, in a reaction vessel, the diamine is first dissolved in a polymerization solvent, and the composition for resin raw materials of the present invention, which is substantially equimolar to the diamine, is slowly added to this solution to carry out the reaction. The temperature at this time is in the range of 0 to 100°C, preferably in the range of 5°C to 80°C, more preferably in the range of 10 to 60°C, even more preferably in the range of 15 to 40°C, and particularly preferably in the range of 20 to 30°C.
[0090] At this time, the concentration of the raw monomer is typically in the range of 5 to 50 weight percent. By performing polymerization within this monomer concentration range, a uniform polyesterimide precursor with a high degree of polymerization can be obtained. If the degree of polymerization of the polyesterimide precursor increases excessively and the polymerization solution becomes difficult to stir, it is also possible to dilute it with the same solvent appropriately.
[0091] There are no particular restrictions on the diamines that can be used, but aromatic diamines and aliphatic diamines may be used.
[0092] As aromatic diamines, specifically, examples include p-phenylenediamine, 3,4'-diaminodiphenyl ether, 4-aminophenyl-4'-aminobenzoate, benzidine, 3,3'-dihydroxybenzidine, 2,2'-bis(trifluoromethyl)benzidine (TFMB), 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)fluorene, etc., and 2,2'-bis(trifluoromethyl)benzidine (TFMB) is particularly preferred.
[0093] Examples of aliphatic diamines include, specifically, 4,4'-methylenebis(cyclohexylamine), 1,4-cyclohexanebis(methylamine), 2,2-bis(4-aminocyclohexyl)propane, 2,2-bis(4-aminocyclohexyl)hexafluoropropane, trans-1,4-diaminocyclohexane, 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, etc.
[0094] As a polymerization solvent that can be used, any solvent may be used as long as the raw monomer, the resulting polyesterimide precursor, and the imidized polyesterimide are dissolved and the reaction is not hindered. Examples include amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; cyclic ester solvents such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, and α-methyl-γ-butyrolactone; carbonate solvents such as ethylene carbonate and propylene carbonate; glycol solvents such as triethylene glycol; phenol solvents such as m-cresol, p-cresol, 3-chlorophenol, and 4-chlorophenol; acetophenone, 1,3-dimethyl-2-imidazolidinone, sulfolane, and dimethyl sulfoxide. Among these, aprotic solvents such as amide solvents, cyclic ester solvents, and carbonate solvents are preferred, and specifically, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, etc. are preferred. In addition, it is preferable to use these solvents that have been dehydrated beforehand.
[0095] When polymerizing a polyesterimide precursor, an aromatic or aliphatic tetracarboxylic acid dianhydride other than the composition for resin raw materials of the present invention, which is a tetracarboxylic acid dianhydride, may be used in combination as a copolymerization component.
[0096] By using the composition for resin raw materials of the present invention, a polyesterimide precursor with high intrinsic viscosity can be obtained compared to the case where conventional raw materials are used.
[0097] <(ii) Process of imidizing polyesterimide precursor>
[0098] Next, the process of imidizing the obtained polyesterimide precursor to obtain polyesterimide is described.
[0099] The imidation method of the polyesterimide precursor may utilize known methods, such as the thermal imidation method involving thermal dehydration and ring closure, or the chemical imidation method using a dehydrating agent. Among these, the chemical imidation method, which allows imidation under mild conditions without requiring high-temperature heat treatment, is preferred.
[0100] In the case of the thermoimidation method, for example, an azeotropic agent with water, such as toluene or xylene, is mixed into the reaction solution of the process for obtaining the aforementioned polyesterimide precursor, and imidation can be performed by reacting while removing by-product water from the system by heating. At this time, the reaction temperature should preferably be heated above the temperature at which water is discharged from the system, for example, above the azeotropic point or above 100°C, 120°C or higher is more preferable, and 130°C or higher is even more preferable. Heating above 150°C is undesirable because the solvent, etc., becomes colored, and this colored component may cause the film to become colored. As another method, a polyesterimide precursor solution obtained by polymerization is spread onto a substrate such as glass and dried to form a film of the precursor. Subsequently, imidation can also be performed by heating the substrate in a range of 200 to 400°C under atmospheric pressure or vacuum.
[0101] In the case of the chemical imidation method, for example, the aforementioned polyesterimide precursor solution is adjusted to a suitable solution viscosity that is easy to stir with the same solvent used during polymerization, and while stirring with a stirrer, a dehydrating ring-closing agent (chemical imidation agent) consisting of an organic acid anhydride and a basic catalyst is mixed to carry out the imidation reaction. At this time, the temperature is in the range of 0 to 100°C, preferably in the range of 5 to 80°C, more preferably in the range of 10 to 60°C, even more preferably in the range of 15 to 40°C, and particularly preferably in the range of 20 to 30°C.
[0102] The organic acid anhydrides that can be used at this time are not particularly limited, but examples include acetic anhydride and propionic anhydride. Acetic anhydride is suitable for use due to the ease of handling and purification of the reagent.
[0103] In addition, basic catalysts are not particularly limited, but pyridine, triethylamine, quinoline, etc., can be used; however, pyridine is suitable for use due to the ease of handling and separation of the reagent.
[0104] The amount of organic acid anhydride in the chemical imidizing agent is in the range of 1 to 10 moles relative to the theoretical dehydration amount of the polyesterimide precursor. In addition, the amount of basic catalyst is in the range of 0.1 to 2 moles relative to the amount of organic acid anhydride.
[0105] Since by-products such as chemical imidizing agents and carboxylic acids are mixed in the reaction solution after the chemical imidization, it is necessary to purify the polyesterimide by removing them. Purification can be performed using known methods. For example, the simplest method involves adding the imidized reaction solution dropwise into a large amount of a solvent (e.g., an alcohol-based solvent such as methanol or ethanol, or an aliphatic hydrocarbon solvent such as hexane) while stirring to precipitate the polyesterimide, and then recovering the polyesterimide powder. If the solid content of the polyimide contained in the reaction solution added dropwise into the solvent is excessively high, the precipitated polyimide may form granules, and impurities may remain in the coarse particles, or it may take a long time to redissolve the obtained polyimide powder in the solvent. On the other hand, if the concentration is made too diluted, a large amount of solvent is required, which may lead to increased environmental burden due to waste solvent treatment or high manufacturing costs. For this reason, a solvent such as the polymerization solvent mentioned above may be added to the liquid after precipitating the polyesterimide. Then, if necessary, a method may be applied to obtain polyesterimide powder by repeatedly washing the powder until by-products are removed, and then drying the powder with the solvent attached under reduced pressure.
[0106] By applying the method for manufacturing polyesterimide according to the present invention, a polyesterimide with high intrinsic viscosity can be obtained compared to cases where conventional raw materials are used. In addition, a polyesterimide can be obtained in which the breaking strength, average elongation at break, and maximum elongation in the tensile strength test results when made into a film are all significantly improved.
[0107] <Preparation of Polyesterimide Solution>
[0108] The obtained polyesterimide can be dissolved in an organic solvent to form a solution.
[0109] This organic solvent can be appropriately selected depending on the intended use or processing conditions of the solution. When continuous coating is performed over a long period of time, the organic solvent in the polyesterimide solution may absorb moisture from the atmosphere, and there is a risk that the polyesterimide may precipitate. Therefore, it is preferable to use a low-hygroscopic solvent such as, for example, triethylene glycol dimethyl ether, γ-butyrolactone, or cyclopentanone.
[0110] The solid content concentration can be appropriately selected according to the use of the solution and is not particularly limited. For example, when making a film, it is preferable to have a solid content concentration of 5 weight% or more, although this varies depending on the molecular weight of the polyesterimide, the manufacturing method, and the thickness of the film being manufactured.
[0111] <Manufacture of Polyesterimide Film>
[0112] Using the obtained polyesterimide solution, polyesterimide can be molded into a film. As a manufacturing method, known methods may be used; for example, a polyesterimide film can be manufactured by applying the polyesterimide solution onto a support such as a glass substrate using a doctor blade, and then drying it.
[0113] In addition, to remove residual deformation, heat treatment can be performed in an inert gas atmosphere or in a vacuum at a temperature of 150 to 300°C.
[0114] Examples
[0115] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples.
[0116] 1. Gel permeation chromatography
[0117] Device: Dososa Manufacturing High-speed GPC Device HLC-8320GPC
[0118] Columns: TSKgel guardcolum HXL-L 1 unit, TSKgel G2000HXL 2 units, TSKgel G3000HXL 1 unit, TSKgel G400
[0119] Flow rate: Pump Sam. 1.0 ml / min, 1 / 3 of Ref. Sam.
[0120] Mobile phase: Tetrahydrofuran
[0121] Column temperature: 40℃ constant
[0122] Detector: Parallax Refractometer (RI)
[0123] An RI detector detects the difference in refractive index between the solution on the sample side and the eluent on the refractive index side, and the refractive index of the solution is correlated with the weight concentration of the solution.
[0124] Sample concentration: 30 mg / 50 ml (tetrahydrofuran solution)
[0125] Injection volume: 100 µl
[0126] 2. Time-of-Flight Mass Spectrometry (TOF-MS)
[0127] Device: Bruker MicroTOFSII TOF-MS device
[0128] Ion source: APCI / Direct probe
[0129] Target ion species: cation
[0130] 3. Intrinsic viscosity
[0131] The reduction viscosity of a 0.5 wt% polyimide precursor solution and a polyimide solution was measured at 30°C using an Ostwald viscometer (manufactured by Shibata Kagaku, SIBATA 026300-1, inner diameter approximately 0.5 mm). This value was considered as the intrinsic viscosity.
[0132] 4. Breaking strength, breaking elongation
[0133] Using a universal material testing machine type 5569 and a load cell of 100 N (manufactured by Instro Japan Company Limited), a tensile test (test speed: 100 mm / min) was performed on a polyimide film specimen (JIS K6251 dumbbell type No. 6), and the breaking elongation (%) was determined from the breaking strength (MPa) and the elongation at which the film broke (test number 5).
[0134] A higher elongation at break indicates higher toughness of the film. Additionally, the breaking strength was calculated from the stress at the time of breakage.
[0135] <Synthesized Example 1>
[0136] In order to prepare the resin raw material compositions of Comparative Examples 1 and 2 below, a resin raw material composition was prepared. The detailed operation method is as follows.
[0137] 53.0 g (0.25 mol) of trimellitic anhydride chloride and 197.4 g of tetrahydrofuran were placed in a 4-neck flask equipped with a thermometer, a stirrer, and a condenser. The flask was then stirred to dissolve the mixture, the vessel was purged with nitrogen, and the mixture was cooled to 5°C or below. Subsequently, a prepared solution containing 40.0 g (0.15 mol) of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, 250.0 g of tetrahydrofuran, and 23.4 g (0.30 mol) of pyridine was added dropwise over 2 hours while maintaining the flask temperature at 5°C or below. After the addition was finished, stirring was performed for 24 hours at 2–8°C. Afterward, water was added at room temperature, and after stirring for 2 hours, the temperature was raised to 40°C and the reaction was carried out for 6 hours. Afterwards, the mixture was cooled to below 10℃ and a large amount of water was added, and a white precipitate was formed. Subsequently, the filtered white precipitate was vacuum dried at 60℃ to obtain 62.5 g of product.
[0138] Subsequently, the obtained product and acetic anhydride were placed in a 4-neck flask and reacted at 100°C for 2 hours. After cooling to room temperature, the mixture was stirred for 24 hours, and a white precipitate was formed. The precipitate was filtered and separated, and then washed with γ-butyrolactone. Afterward, it was dried under reduced pressure at 120°C for 1 hour and at 150°C for 1 hour. Additionally, the obtained precipitate was washed with γ-butyrolactone by holding at 100°C for 1 hour, cooled, filtered and separated, and then dried under reduced pressure at 150°C for 2 hours.
[0139] The white solid obtained in this manner was subjected to gel permeation chromatography (GPC) RI analysis and TOF-MS analysis, respectively. As a result, the obtained resin raw material composition contained 87.7 area% of compound a as component A of the present invention and 10.4 area% of the sum of compounds b1 and b2 as component B of the present invention. In addition, from the detection of the molecular weight of the Exact Mass of compound b1 (E / Z = 444) and the molecular weight of the Exact Mass of compound b2 (E / Z = 486) by TOF-MS analysis, it was confirmed that the compounds had the chemical structural formulas of (b1) and (b2) in the chemical formula below.
[0140]
[0141] <Example 1>
[0142] A composition for resin raw materials according to the present invention was prepared. The detailed operation method is as follows.
[0143] 411.8 g (1.96 mol) of trimellitic anhydride chloride and 1213.0 g of tetrahydrofuran were placed in a 4-neck flask equipped with a thermometer, a stirrer, and a condenser. While stirring to dissolve, the container was purged with nitrogen and cooled to 5°C or below. Subsequently, a prepared solution containing 229.8 g (0.85 mol) of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, 1545.0 g of tetrahydrofuran, and 336.2 g (4.25 mol) of pyridine was added dropwise over 2 hours while maintaining the temperature inside the flask at 5°C or below. After the addition was finished, stirring was performed for 2 hours at 5°C or below (post-stirring 1). Subsequently, the temperature was raised to 65°C and stirring was performed for 3 hours (post-stirring 2).
[0144] After the reaction was completed, the mixture was cooled to 40°C while stirring, 200.0 g of water was added, and the mixture was maintained at 40°C for 14 hours. Subsequently, the mixture was cooled to 25°C, and the resulting precipitate was filtered. Then, the product and acetic anhydride were placed in a 4-neck flask, maintained at 100°C for 2 hours, cooled to 25°C, and the resulting precipitate was filtered. Additionally, the filtered precipitate was washed with γ-butyrolactone in a slurry state at 120°C and filtered at 25°C. The filtered precipitate was further washed with cyclohexanone in a slurry state at 100°C and filtered at 25°C. The filtered precipitate was dried by raising the temperature to 100°C under reduced pressure.
[0145] Gel penetration chromatography (GPC) RI analysis was performed on the white solid obtained in this manner. As a result, it was clear that the composition for resin raw materials of the present invention contains 99.4 area% of compound a as component A and 0.1 area% of the sum of compounds b1 and b2 as component B of the present invention.
[0146] (Polymerization of polyimide precursors)
[0147] 1.284 g (4.01 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) was dissolved in 33.784 g of dehydrated N,N'-dimethylacetamide (DMAc). To this, 2.469 g (3.97 mmol) of the resin raw material composition of Example 1 was slowly added, and the mixture was stirred at room temperature for 72 hours to obtain polyamide acid, which is a polyimide precursor (solid content 10.0 wt%). The intrinsic viscosity of the obtained polyamide acid was 5.01 dL / g.
[0148] (Chemical imidation reaction)
[0149] The obtained polyamide acid was diluted with dehydrated dimethylacetamide to a solid content of 6.5 wt%. To this, a mixed solution of 24.69 mmol of acetic anhydride and 12.35 mmol of pyridine was slowly added dropwise at room temperature while stirring, and stirring was continued for an additional 24 hours after the addition was finished. The obtained polyimide solution was slowly added dropwise to a large amount of methanol. Dimethylacetamide was additionally added to precipitate fibrous polyimide, and then the mixture was filtered. The obtained white precipitate was washed with methanol and dried under vacuum at 60°C.
[0150] (Preparation of polyimide solution and formation of polyimide film)
[0151] The above polyimide powder was redissolved in cyclopentanone at room temperature to prepare a homogeneous solution of 5.1 wt%. This polyimide solution was applied to a glass substrate and dried in a hot air dryer at 60°C for 2 hours. Subsequently, the substrate was heat-treated in a vacuum at 250°C for 1 hour, cooled to room temperature, and then the film was peeled off from the glass substrate. The polyimide film was heat-treated once more in a vacuum at 250°C for 10 minutes to remove residual deformation. The obtained polyimide film was almost colorless and transparent.
[0152] The mechanical properties of this polyimide film (film thickness 20 μm) were measured. The results are shown in Table 1 below.
[0153] <Example 2>
[0154] To evaluate the effect of the content of component B, the composition for resin raw materials of the present invention obtained in Example 1 and the composition for resin raw materials obtained in Synthesis Example 1 were mixed by weight such that the content of component B was 0.3 area% (wherein compound a was 99.3 area%). Polymerization of the polyimide precursor was performed in the same manner as in Example 1, and the intrinsic viscosity at 52 hours was 4.39 dL / g, and the intrinsic viscosity at 72 hours was 4.46 dL / g. Subsequently, a chemical imidization reaction and the production of a polyimide film were performed in the same manner as in Example 1, and mechanical properties were measured. The results are shown in Table 1 below.
[0155] <Comparative Example 1>
[0156] A composition was prepared by mixing by weight in the same manner as in Example 2, such that the content of component B was 1.0 area% (wherein compound a was 98.4 area%). Polymerization of the polyimide precursor was carried out in the same manner as in Example 1, and the intrinsic viscosity at 52 hours was 3.29 dL / g, and the intrinsic viscosity at 72 hours was 3.30 dL / g. Subsequently, a chemical imidization reaction and the fabrication of a polyimide film were carried out in the same manner as in Example 1, and mechanical properties were measured. The results are shown in Table 1 below.
[0157] <Comparative Example 2>
[0158] A composition was prepared by mixing so that the content of component B was 0.5 area%, in the same manner as in Example 2 (wherein compound a was 98.9 area%). Polymerization of the polyimide precursor was carried out in the same manner as in Example 1, and the intrinsic viscosity at 52 hours was 4.24 dL / g, and the intrinsic viscosity at 72 hours was 4.26 dL / g. Subsequently, a chemical imidization reaction and the fabrication of a polyimide film were carried out in the same manner as in Example 1, and mechanical properties were measured. The results are shown in Table 1 below.
[0159] <Comparative Example 3>
[0160] The manufacturing method described in “Synthetic Example 1” of the above Patent Document 2 was further tested, and gel penetration chromatography (GPC) RI analysis was performed on the recrystallized body obtained through the “purification” process. As a result, the composition contained 96.4 area% of compound a as component A of the present invention and 1.8 area% of the sum of compounds b1 and b2 as component B of the present invention. In addition, the chemical structures of compounds b1 and b2 were also confirmed to be the same as those in Example 1.
[0161] The "intrinsic viscosity of polyamide acid," "intrinsic viscosity of polyimide," and mechanical properties of the polyimide film described in "Example 1" (paragraphs 0065–0067) of the above Patent Document 2 are described in Table 1 below with the symbol "※". Since the film thickness and test conditions differ from those of Examples 1 and 2 and Comparative Examples 1 and 2, these mechanical properties cannot be simply compared, but they are described as reference values.
[0162]
[0163] From the results of Table 1, it became clear that when the resin raw material compositions of Examples 1 and 2 containing specific amounts of component A and component B of the present invention are used, the intrinsic viscosity of the polyamide acid and polyimide obtained is increased compared to the resin raw material compositions of Comparative Examples 1 to 3, in which the content of the main component A is low and the content of the impurity component B is high, and also the average breaking strength, maximum breaking strength, average breaking elongation, and maximum breaking elongation in the tensile strength test results of the polyimide film obtained are all significantly improved.
Claims
Claim 1 A composition for a resin raw material containing, as component A, a compound represented by the following chemical formula a, and as component B, a compound represented by the following chemical formula b, in the following compositional ratios. [Compositional Ratio]: With respect to the total amount of all components detected by measurement using gel permeation chromatography with a differential refractometer as the detector, component A is 99.0 area% or more and 99.99 area% or less, and component B is 0.005 area% or more and 0.4 area% or less. [Chemical Formula a] [Chemical formula b] (In the formula, R represents a hydrogen atom or R1-CO- (where R1 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms). Claim 2 A method for manufacturing polyesterimide, comprising a process (i) of obtaining a polyesterimide precursor by reacting a composition containing, in the following compositional ratios, a compound represented by the chemical formula a as component A and a compound represented by the chemical formula b as component B, with a diamine, and subsequently a process (ii) of imidizing the same. [Compositional Ratio]: With respect to the total amount of all components detected by measurement by gel permeation chromatography using a differential refractometer as a detector, component A is 99.0 area% or more and 99.99 area% or less, and component B is 0.005 area% or more and 0.4 area% or less. [Chemical Formula a] [Chemical formula b] (In the formula, R represents a hydrogen atom or R1-CO- (where R1 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
Citation Information
Patent Citations
Polyimide and molded body thereof
WO2014046180A1
